Hubungan Persepsi Perawat Pelaksana Tentang Gaya Kepemimpinan Kepala Ruangan dengan Indikator Mutu Pelayanan Rumah Sakit - Lilis Rohayani; Andria Pragholapati (NHM PRESS, 2020)
Professional hospital services are supported by several things, one of which is good and situational managerial leaders and efficient use of facilities and infrastructure in accordance with predetermined ideal value standards. A nurse is required to have a holistic ability, one of which is the head of the room, which must coordinate between nursing care services and service administration, one of which is hospital service quality indicators to measure the efficiency of hospital services and facilities so as to create professional services. The purpose of this study was to determine the relationship between the leadership style of the room head and hospital service quality indicators. The research method used is Analytical Survey with Cross Sectional design. The population in this study were 85 nurses and the sample used was 70 because of using Purposive Sampling. The research was conducted using questionnaires and observations, questionnaires were given directly to the nurse nurses at the same time and observations for 14 days. Data was obtained directly using a valid questionnaire and from observations the calculation of hospital service quality indicators, then the data were analyzed by Univariate by looking at the percentage description of leadership style and indicators of hospital service quality while Bivariate used an alternative Chi Square test with Kolmogorov Smirnov test. The results of the study showed that there was nothing a relationship between the leadership style of the room head and the hospital service quality indicator (Pvalue = 1,083 >0.05 (α)). It is expected that the head of the room can apply a situational leadership style.